2005
DOI: 10.1002/ejlt.200401072
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the predominant polymorphic form of mango ( Mangifera indica ) almond fat by differential scanning calorimetry and X‐ray diffraction

Abstract: In this paper, some important properties, from the application point of view, of mango (Mangifera indica) almond fat var. Manila (MAF) were analyzed by differential scanning calorimetry and X-ray diffraction techniques. The thermal profile, the solid fat content (SFC) and the predominant polymorphism of MAF samples, previously characterized chemically, were studied. The results showed that this fat, from one of the main residues of mango industrialization, had a relatively simple fusion/crystallization behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…The X-ray diffraction patterns reported here indicated that the all four MKFs solidified into a mixture of pseudo-β', β', sub-β and β polymorphs after the static crystallization at 20 for 2 h. This was in agreement with what was observed with the polymorphic behavior of MKF from Kaew variety by Sonwai et al 8 and from Manila variety by Solís-Fuentes et al 23 . The peak at 4.2 Å, which was associated with β' polymorph, showed the strongest diffraction intensity in all fat samples, indicating that β' was the predominant polymorph for all MKFs under these crystallization conditions.…”
Section: Static Crystallization Behaviorsupporting
confidence: 91%
“…The X-ray diffraction patterns reported here indicated that the all four MKFs solidified into a mixture of pseudo-β', β', sub-β and β polymorphs after the static crystallization at 20 for 2 h. This was in agreement with what was observed with the polymorphic behavior of MKF from Kaew variety by Sonwai et al 8 and from Manila variety by Solís-Fuentes et al 23 . The peak at 4.2 Å, which was associated with β' polymorph, showed the strongest diffraction intensity in all fat samples, indicating that β' was the predominant polymorph for all MKFs under these crystallization conditions.…”
Section: Static Crystallization Behaviorsupporting
confidence: 91%
“…The crystallization of Fig. 5 X-ray diffraction patterns of (a) mango kernel fat, (b) palm oil mid-fraction, (c) recommended cocoa butter equivalent, (d) cocoa butter and (e) a mixture of cocoa butter quivalent and cocoa butter during crystallization at 20°C for 60 min under static conditions MKF into a mixture of crystal structures reported here is in agreement with the crystallization behavior of the MKF at 22°C published by Solis-Fuentes et al (2005), where MKF was found to crystallize into a mixture of β′, pseudo-β′, sub-β and β structures under quiescent conditions over a long period of 26 days.…”
Section: Compatibility Between Cbe and Cbsupporting
confidence: 87%
“…The β crystals are the most stable and are transitions of the above forms (Hagemann, 1988). In regard to such transitions, the molecular mobility, stability and their relationships are critical aspects for controlling the quality of the fatty products that are elaborated with these materials (Roos, 1995;Solís-Fuentes et al, 2005). The vast majority of phase transitions of lipids in foods, drugs and cosmetics associated with the behavior of processing, storage and use are established between the solid and liquid states and the different polymorphic forms of these materials (Roos, 1995;Sato, 1999).…”
Section: Msso Dry Fractionation and Thermal Behavior Of Its Fractionsmentioning
confidence: 99%